ANALISIS RANCANGAN PENGEMBANGAN WEBSITE ALUMNI MENGGUNAKAN METODE CUSTOMER KNOWLEDGE MANAGEMENT DI UNIVERSITAS YAPIS PAPUA JAYAPURA - Prayitno, Joko; Kusrini, Kusrini; Sudarmawan, Sudarmawan (Informasi Interaktif, 2018)
Alumni Association of an educational institution currently requires the website as a means of publication, information and connections in carrying out its activities. With a reliable alumni website is expected to facilitate all alumni activities both related to education and teaching and community serviceIn this research will be done alumni website development by designing interface in the form of mockups that allows users to connect and perform mutualism symbiotic activity. The development of alumni website is done using Customer Knowledge Management (CKM) method, with Customer Relationships Managemet (CRM) phase and Knowledge Management (KM) process which focuses on interface perspective.CKM method is a combination of CRM and KM, while CKM is related to knowledge and relationship, which are two key in business. On the one hand, it can create a closer and valuable symbiotic relationship with the customer, and on the other hand, the knowledge and professional experience gained from communication with the customer can be poured into the maximum product and service, so that it can be the foundation for profit in the competition. Keyword: Website, Alumni, CKM, CRM, KM